2023
DOI: 10.1371/journal.pone.0295384
|View full text |Cite|
|
Sign up to set email alerts
|

Time trends in self-reported depressive symptoms, prescription of antidepressants, sedatives and hypnotics and the emergence of social media among Norwegian adolescents

Lars Lien,
Tore Bonsaksen,
Tonje Holte Stea
et al.

Abstract: Background Research has shown increased mental health problems and use of prescription drugs among adolescents in recent years and social media use has been linked to poorer mental health. However, trend studies concerning these topics are scarce. The purpose of this study was to analyze gender-specific trends in a) symptoms of depression and loneliness, and b) prescription of antidepressants, hypnotics and sedatives, in relation to the emergence of social media among adolescents in Norway. Methods This is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…A general increase in psychological problems is also evident from self-reporting in surveys among Norwegian adolescents [15,24,25], and this may be associated with the increased use of hypnotic drugs observed in our study. A recent ecological study by Lien et al also showed a significant upward trend in self-reported depressive symptoms and hypnotic drug use over recent decades following the introduction of social media platforms in Norway [26].…”
Section: Discussionmentioning
confidence: 95%
“…A general increase in psychological problems is also evident from self-reporting in surveys among Norwegian adolescents [15,24,25], and this may be associated with the increased use of hypnotic drugs observed in our study. A recent ecological study by Lien et al also showed a significant upward trend in self-reported depressive symptoms and hypnotic drug use over recent decades following the introduction of social media platforms in Norway [26].…”
Section: Discussionmentioning
confidence: 95%